Genetic Diversity Loss in Chironomus sancticaroli (Diptera: Chironomidae) Exposed to Pyrimethanil Fungicide: an Analysis Using RAPD Technique - Colombo-Corbi, Vanessa; Gorni, Guilherme Rossi; Sanzovo-Falcoski, Thais [UNESP]; Costa, Paulo Inácio [UNESP]; Corbi, Juliano J. (Springer Nature, 2017)
In the agricultural cultivation, the Pyrimethanil (4,6-dimethyl-N-phenyl-2-pyrimidinamine) fungicide is one of the most widely used compound in monocultures and has been detected in aquatic ecosystems. These genotoxic products increase the frequency of lesions in the DNA molecule, thereby increasing the risk of replication and transcription of altered DNA sequences. This study aimed to assess the loss of genetic diversity of Chironomus sancticaroli, a Brazilian native insect species, exposed to Pyrimethanil fungicide, using RAPD-PCR (random amplified polymorphic DNA) technique. The results showed that there was significant loss in the genetic diversity in the organisms exposed to high Pyrimethanil concentrations when compared with control site. Our findings reveal that RAPD-PCR is an effective method to access genetic loss derived to fungicide use and that the agriculture application may lead to a decrease in aquatic biota genetic diversity. This finding has important implications for conservation strategies and ecological management environments.
Keywords: Agriculture cultivation; Chironomidae; Genetic diversity; Stream